Comparison of the Number of Bacterial Colonies Before and After Using Hand Sanitizer From Acacia Nilotica Leaf Extract : Perbandingan Jumlah Koloni Bakteri Sebelum Dan Sesudah Menggunakan Hand Sanitizer Dari Ekstrak Daun Acacia nilotica L. - Jannah, Syarifah Miftahul El; Zuraida, Zuraida; Yulfianna, Desy; Aditia, Erie (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Background: Using hand sanitizers was an act of necessity during the Covid-19 pandemic. With this action, it is expected to control the number of bacterial colonies on the palms of the hands. One of the herbal ingredients that can inhibit the growth of germs is Acacia nilotica L-leaf extract so that it can be used as an active ingredient in hand sanitizer. Objective: To determine the number of bacterial colonies before and after using a hand sanitizer with the active ingredient of acacia leaf extract. Materials and Methods: The study used random sampling analysis before and after treatment. Acacia nilotica leaf ethanol extract formula 10%, 20% and 30%. Each concentration was used by 11 men and 11 women as a hand sanitizer with movements according to WHO standards and left for 30 seconds. Check the count of germs on hands before and after using hand sanitizer. Results: The highest decrease in the number of bacterial colonies was found at a concentration of 30% reaching 64.84% in men and 89.61% in women. There were differences in the ability to decrease the number of bacterial colonies from each concentration (P 0.003 < 0.005). Conclusion: Acacia nilotica L leaf extract can be a candidate for active hand sanitizer ingredients.